Innovative molecular-based fluorescent nanoparticles for multicolor single particle tracking in cells. (20th January 2016) - Daniel, Jonathan; Godin, Antoine G; Palayret, Matthieu; Lounis, Brahim; Cognet, Laurent; Blanchard-Desce, Mireille
Abstract: Based on an original molecular-based design, we present bright and photostable fluorescent organic nanoparticles (FONs) showing excellent colloidal stability in various aqueous environments. Complementary near-infrared emitting and green emitting FONs were prepared using a simple, fast and robust protocol. Both types of FONs could be simultaneously imaged at the single-particle level in solution as well as in biological environments using a monochromatic excitation and a dual-color fluorescence microscope. No evidence of acute cytotoxicity was found upon incubation of live cells with mixed solutions of FONs, and both types of nanoparticles were found internalized in the cells where their motion could be simultaneously tracked at video-rate up to minutes. These fluorescent organic nanoparticles open a novel non-toxic alternative to existing nanoparticles for imaging biological structures, compatible with live-cell experiments and specially fitted for multicolor single particle tracking.